Attitudes Towards Blended Learning : A Study of Leadership Training Education (Diklat PIM) IV Year 2018 Training Participants - Nadya Megawati Rachman; Caterin Magdalena Simamora; Ratnaningsih Hidayati (Jurnal Sosiologi Pendidikan Humanis, 2021)
The advancement of information technology is one of the driving factors for implementing e-Government. Nevertheless, the learning process in government official capacity development is now conceivably conducted online. This research aims to discover government officials' attitudes towards blended learning in a population of 40 respondents of Leadership Training Education or   Diklat PIM IV in 2018. This research is conducted with a quantitative methodology approach. The T-test used to test the first research hypotheses. A one-way ANOVA was performed for examining the second and third hypotheses. The result shows there is a favorable attitude towards blended learning among the Diklat PIM IV 2018 training participants. There are significant differences in attitudes toward blended learning based on gender but there is no significant difference in attitudes towards blended learning based on age classification.